2014
DOI: 10.1016/j.fm.2014.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity and dynamics of Spanish-style green table-olive fermentations in large manufacturing companies through culture-dependent techniques

Abstract: Microbial diversity and dynamics of Spanish-style green table-olive fermentations in large manufacturing companies through culture-dependent techniques, Food Microbiology (2014Microbiology ( ), doi: 10.1016Microbiology ( /j.fm.2014 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 55 publications
2
37
2
Order By: Relevance
“…Besides this, there was a considerable genetic diversity of LAB species colonizing the olive surface, mainly at 8% NaCl. Lucena-Padrós et al (2014) have confirmed this microbial diversity at industrial scale in a recent survey carried out at several locations; the spontaneous fermentation was dominated by L. pentosus , but there was always a diverse secondary microbiota, including some new bacterial species. In fact, the actual processing conditions prevailing in the current fermentation yards together with the industrial high volume vessels with considerable brine surface exposed to air makes difficult the survival of any starter culture over the environmental microbiota by just controlling the physicochemical conditions.…”
Section: Resultssupporting
confidence: 64%
“…Besides this, there was a considerable genetic diversity of LAB species colonizing the olive surface, mainly at 8% NaCl. Lucena-Padrós et al (2014) have confirmed this microbial diversity at industrial scale in a recent survey carried out at several locations; the spontaneous fermentation was dominated by L. pentosus , but there was always a diverse secondary microbiota, including some new bacterial species. In fact, the actual processing conditions prevailing in the current fermentation yards together with the industrial high volume vessels with considerable brine surface exposed to air makes difficult the survival of any starter culture over the environmental microbiota by just controlling the physicochemical conditions.…”
Section: Resultssupporting
confidence: 64%
“…However, this specie has been frequently detected on brines at the later phase (Lucena-Padr os et al, 2014) or throughout (Bautista-Gallego et al, 2011) the Spanish-style green olive fermentation process. Although P. manshurica was only detected in brine at the beginning of the fermentation (first 4 days), several authors have yet reported its presence in brines throughout (Abriouel et al, 2011) and at later stages (Lucena-Padr os et al, 2014;Nisiotou et al, 2010) of the fermentation of several table olive types.…”
Section: Yeast Dynamics During Fermentationmentioning
confidence: 99%
“…[3] The EU member states cover only the 31% of this world production whereas they produce the 68% of that of olive oil. [8][9][10] In laboratory scale studies for the Spanish style processing dependence on cultivar characteristics in terms of fruit quality attributes, nutrients and polar phenolic and related compounds, conditions of lye treatment and different fermentation parameters (spontaneous vs. inoculated, salt content, antimicrobial compounds) was evidenced. There is a distinctive difference among these three countries regarding their current production capability.…”
Section: Introductionmentioning
confidence: 99%